Culture of National Philosophical Communities: the Project Dedicated to the Research of Modern Ukrainian Philosophical Traditions - Lidiya Bogataya (International Society of Philosophy and Cosmology, 2018)
The article introduces a new Ukrainian research project related to the preparation of a collective monograph. This monograph will highlight the activities of modern Ukrainian philosophical communities. Such communities in their totality constitute a modern national philosophical culture and its study belongs to the category of macro-humanitarian research. The basis for a holistic observation of a culture is, on the one hand, digital technologies that enable technically to take into account practically all the studies that are carried out in a particular field in a certain period of time. On the other hand, new methodological developments are emerging that allow us to quickly process large text arrays. An example of such methodological innovations can be considered the study of American-Italian literary critic Franco Moretti. Moretti examines the opportunities that arise when using "distant reading." The article emphasizes that the main advantage of "distant reading" is the possibility of taking into account the whole body of texts, and not only its canonical kernel. Introduces the idea of «compression reading» as a special kind of "rapid reading", which allows you to get the most general idea of the text based on the analysis of the title of the text and its annotation. The development of compression reading technologies along with distant reading technologies will allow efficient and efficient processing of large array of texts. The expediency of actualization of the whole textual array formed in this or that humanitarian field of research is associated with the development of a new ethic. This ethic is the ethic of collective labor. A new understanding of the collective is considered, which is possible only with careful consideration of any manifestation of the individual